The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24119515
|View full text |Cite
|
Sign up to set email alerts
|

The Small RNA-Binding Protein CcaF1 Promotes Formation of Photosynthetic Complexes in Rhodobacter sphaeroides

Abstract: In natural habitats, bacteria frequently need to adapt to changing environmental conditions. Regulation of transcription plays an important role in this process. However, riboregulation also contributes substantially to adaptation. Riboregulation often acts at the level of mRNA stability, which is determined by sRNAs, RNases, and RNA-binding proteins. We previously identified the small RNA-binding protein CcaF1, which is involved in sRNA maturation and RNA turnover in Rhodobacter sphaeroides. Rhodobacter is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recent studies of our group identified a novel small RNA‐binding protein, CcaF1, which is co‐expressed with four homologous CcsR sRNAs (CcsR1‐4) from a single promoter (Billenkamp et al, 2015; Grützner, Billenkamp, et al, 2021). While CcaF1 binds to various RNA targets (Grützner, et al, 2023; Grützner, Billenkamp, et al, 2021), affecting their stability and regulating gene expression, the CcsR sRNAs inhibit a glutathione‐dependent C1 metabolic pathway, leading to increased levels of antioxidative glutathione, which provides protection against reactive oxygen species and enhancing cell viability. Previous work documented a direct correlation between CcsR levels and stress resistance (Billenkamp et al, 2015; Grützner, Billenkamp, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of our group identified a novel small RNA‐binding protein, CcaF1, which is co‐expressed with four homologous CcsR sRNAs (CcsR1‐4) from a single promoter (Billenkamp et al, 2015; Grützner, Billenkamp, et al, 2021). While CcaF1 binds to various RNA targets (Grützner, et al, 2023; Grützner, Billenkamp, et al, 2021), affecting their stability and regulating gene expression, the CcsR sRNAs inhibit a glutathione‐dependent C1 metabolic pathway, leading to increased levels of antioxidative glutathione, which provides protection against reactive oxygen species and enhancing cell viability. Previous work documented a direct correlation between CcsR levels and stress resistance (Billenkamp et al, 2015; Grützner, Billenkamp, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that the small RNA‐binding DUF1127‐domain protein CcaF1 promotes the formation of photosynthesis complexes in R. sphaeroides (Grützner et al, 2023). ccaF1 is co‐transcribed with the CcsR sRNAs and also shows higher levels in the rnc − mutant.…”
Section: Discussionmentioning
confidence: 99%